A COMPARISON OF GENDER DIFFERENCES TOWARD MATHEMATICS’ COGNITIVE LEARNING OUTCOMES IN A MIDDLE SCHOOL - Avianty, Octaviana; Manogu, Ridwanta; Lestari, Meiva Marthaulina (Universitas Pelita Harapan, 2018)
This research examined whether there is any difference of performing mathematics in the topic of Indices & Surds on cognitive learning outcomes between female and male students in grade 9. The research method used was causal-comparative, conducted in t-test for independent means to represent the comparison of mathematics’ cognitive learning outcomes between female and male students, with the significance level 5%. There were 113 respondents who were selected using the convenience sampling technique and they consisted of 68 female students and 45 male students. There were two independent means samples that were going to be compared. The instrument used to obtain students’ demographic characteristics of gender and students’ mathematics cognitive learning outcomes in the topic of Indices & Surds was their score list in midterm report card. Based on the result, it was obtained that 1.69 less than (1.69 < 1.98). Therefore, Ho is accepted, means that there is no mean score differences in mathematics’ cognitive learning outcomes in the topic of Indices & Surds between grade IX female students and grade 9 male students. Thus, the conclusion is that gender as a causal factor in this research gave no difference towards grade 9 students’ cognitive learning outcomes, particularly in mathematics ability in the topic of Indices & Surds in ABC Middle School.BAHASA INDONESIA ABSTRAK: Tujuan dari penelitian ini adalah untuk melihat apakah ada perbedaan nilai rata-rata dari hasil belajar kognitif matematika pada topik pangkat dan akar antara siswa perempuan kelas IX dan siswa laki-laki kelas IX. Metode penelitian yang digunakan adalah kausal-komparatif, dilaksanakan dengan teknik t-test for independent means untuk merepresentasikan perbandingan hasil belajar kognitif matematika antara siswa laki-laki dan siswa perempuan, dengan taraf signifikansi 5%. Terdapat 113 responden yang dipilih dengan teknik convenience sampling; terdiri dari 68 siswa perempuan dan 45 siswa laki-laki, sebagai dua sample rata-rata independen yang akan dibandingkan. Instrument yang digunakan untuk memperoleh data demografis jenis kelamin siswa dan data hasil belajar kognitif matematika siswa pada topik pangkat dan akar adalah daftar nilai di buku raport tengah semester. Dari hasil penelitian, diperoleh t obt , yaitu 1.69 dimana kurang dari t cv (1.69<1.98). Ho diterima, yang berarti tidak terdapat perbedaan nilai rata-rata dari hasil belajar kognitif matematika pada topik pangkat dan akar antara siswa perempuan kelas IX dan siswa laki-laki kelas IX. Sehingga, dapat diambil kesimpulan bahwa jenis kelamin sebagai kausal faktor dalam penelitian ini tidak memberikan perbedaan terhadap hasil belajar kognitif siswa kelas IX, khususnya dalam kemampuan matematika pada topik pangkat dan akar di Sekolah Menengah ABC.